Urinary drug metabolite testing in chronic heart failure patients indicates high levels of adherence with life‐prolonging therapies. (11th March 2021) - Sweeney, Mark; Cole, Graham D.; Pabari, Punam; Hadjiphilippou, Savvas; Tayal, Upasana; Mayet, Jamil; Chapman, Neil; Plymen, Carla M.
Abstract: Aims: Despite medical therapy for heart failure (HF) having proven benefits of improving quality of life and survival, many patients remain under‐treated. This may be due to a combination of under‐prescription by medical professionals and poor adherence from patients. In HF, as with many other chronic diseases, adherence to medication can deteriorate over time particularly when symptoms are well controlled. Therefore, detecting and addressing non‐adherence has a crucial role in the management of HF. Significant flaws and inaccuracies exist in the methods currently used to assess adherence such as patient reporting, pill counts, and pharmacy fill records. We aim to use high‐performance liquid chromatography–tandem mass spectrometry (HPLC‐MS) to detect metabolites of HF medications in the urine samples of chronic HF patients. Methods and results: Urine samples were collected from 35 patients in a specialist HF clinic. Patients were included if they had an ejection fraction <45% and were taking at least two disease‐modifying HF medications. They were excluded if they had been admitted to hospital for HF in the 3 months preceding clinic attendance. These samples were sent for HPLC‐MS and tested for all HF medications prescribed for that patient. A high rate of complete adherence of 89% was detected in these patients, with 94% being partially adherent (at least one HF medication detected) to therapy (at least one HF medication detected). This analysis also highlighted that mineralocorticoid antagonists represent both the most under‐prescribed (67%) and poorly adhered (75%) medication class. Conclusions: This analysis revealed a surprisingly high level of adherence to disease‐modifying therapy in chronic HF patients and highlights that most of our 'total' under‐treatment is likely to be from a failure to prescribe rather than a failure to adhere. Testing for metabolites of disease‐modifying HF drugs in urine using HPLC‐MS is feasible and is a useful adjunct to a specialist HF service. At present, the distinction between treatment failure and failure to take treatment is not always clear, which is important because the investigation and potential solutions are different. The former needs initiation of additional therapies and consideration of additional diagnoses, whereas the latter requires strategies to understand reasons underlying poor adherence and collaborative working to improve this: the wrong strategy will be ineffective.